The prevalence of multidrug-resistant Mycobacterium tuberculosis in patients diagnosed with pulmonary TB at Ngwelezana Hospital. A quantitative cross-sectional retrospective. - Magubane, Nonduduzo; Shangase, Simangaliso (Student’s Journal of Health Research Africa, 2025)
Introduction Multidrug-resistant tuberculosis (MDR-TB), which is TB resistant to critical anti-TB drugs such as isoniazid and rifampicin, presents a major challenge to tuberculosis treatment, leading to significant public health concerns. The study objective is to evaluate the patterns of antibiotic drug resistance of MTB in patients taking treatment for TB and determine the demographic profile of patients in whom drug-resistant TB is the most prevalent. Aim This research aims to determine the prevalence of drug resistance in patients with Mycobacterium tuberculosis using retrospective data. Methodology This study aimed to evaluate the prevalence of multidrug-resistant tuberculosis by analyzing retrospective data from the National Health Laboratory Services for patients diagnosed at Ngwelezana Hospital, KwaZulu-Natal. A sample of 695 participants was included in the study, with 267 (38.4%) males and 428 (61.6%) females. Among these participant’s demographic characteristics of patients tested for TB were evaluated, and an analysis was done to explore the rifampicin susceptibility. Findings The study correlation analysis revealed a weak but statistically significant positive correlation between age and gender (ρ = 0.077, p = 0.022). Rifampicin resistance was detected in 5.3% of the tested participants, while 94.7% were found to be sensitive to the drug. The relatively low prevalence of rifampicin resistance is a positive finding, suggesting that first-line TB treatment with rifampicin remains largely effective in this population. However, the presence of any resistance is still a cause for concern, as rifampicin-resistant TB can lead to more complex and expensive treatment regimens, with higher morbidity and mortality rates. Conclusion The study’s findings indicate the low prevalence of rifampicin resistance, but continuous monitoring is necessary to prevent the spread of resistant strains. Future research should include exploring track changes in rifampicin resistance over time and investigating potential contributors to its resistance.